Clinical applications of serum tissue inhibitor of matrix metalloproteinase 3 and sex determining region Y box protein 2 for an early diagnosis of renal injury in type 2 diabetes mellitus - Hong-li Zhang; Hai-cheng Wang; Hua Li; Rui-chao Wei; Ling Zeng (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the roles of serum tissue inhibitor of matrix metalloproteinase 3（TIMP3） and sex determining region Y box protein 2（SOX2） in an early diagnosis of renal injury in type 2 diabetes mellitus（T2DM）. Methods From April 2022 to April 2023， 102 T2DM patients visiting General Hospital of North China Petroleum Administration Bureau were recruited as research subjects. Based upon 24 h serum urinary protein excretion rate（UAER）， they were assigned into two groups of renal injury（n = 40） and renal non-injury（n = 62）. Another 50 patients undergoing health examinations at General Hospital of North China Petroleum Administration Bureau were regarded as control group. Enzyme-linked immunosorbent assay（ELISA） was utilized for measuring the serum levels of TIMP3 and SOX2. General profiles， serum levels of TIMP3， SOX2， glycosylated hemoglobin（HbA1c）， UAER， serum creatinine（Scr） and glomerular filtration rate（eGFR） of three groups were compared. Pearson's correlation was utilized for examining the relationship between serum TIMP3/SOX2 and HbA1c， UAER， Scr and eGFR. Receiver operating characteristic curve（ROC） was applied for examining the diagnostic value of serum TIMP3/SOX2 for renal injury in T2DM patients. Results The serum levels of TIMP3 [（0.68 ± 0.17）μg/L vs （1.35 ± 0.35）μg/L] and eGFR [（105.99 ± 20.56）mL·min−1·（1.73 m2）−1 vs （133.15 ± 26.18）mL·min−1·（1.73 m2）−1] were obviously lower in T2DM patients than those in control group（P＜0.05）. Serum levels of TIMP3 [（0.47 ± 0.11）μg/L vs （0.82 ± 0.21）μg/L] and eGFR [（74.69 ± 10.22）mL·min−1·（1.73 m2）−1 vs （126.18 ± 27.23）mL·min−1·（1.73 m2）−1] were obviously lower in patients with renal injury than those without（P＜0.05）. Serum levels of SOX2 [（8.91 ± 1.82）kU/L vs （5.15 ± 1.31）kU/L]， HbA1c[（8.80 ± 1.55）% vs （5.52 ± 0.83）%]， UAER [（70.13 ± 18.06）mg/24 h vs （13.22 ± 3.61）mg/24 h] and Scr [（82.14 ± 15.23）µmol/L vs （53.19 ± 5.62）µmol/L] were obviously higher than those in control group（P＜0.05）. Serum levels of SOX2 [（10.81 ± 2.13）kU/L vs （5.15 ± 1.31）kU/L]， UAER [（156.83 ± 40.29）mg/24 h vs （13.22 ± 3.61）mg/24 h] and Scr [（113.77 ± 13.58）µmol/L vs （53.19 ± 5.62）µmol/L] were obviously higher in patients with renal injury than in patients without（P＜0.05）. Pearson's correlation analysis revealed that TIMP3 was obviously correlated negatively with HbA1c， UAER and Scr（P＜0.05） and positively with eGFR（P＜0.05）. SOX2 was obviously correlated positively with HbA1c， UAER and Scr（P＜0.05） and negatively with eGFR（P＜0.05）. An obvious negative correlation existed between serum TIMP3 and SOX2（r = −0.590，P＜0.05）. The results of ROC indicated that the sensitivity and specificity of serum TIMP3 plus SOX2 in the diagnosis of renal injury in T2DM patients were 95.0% and 85.3% respectively. Both were obviously higher than those of TIMP3 and SOX2 alone. Conclusions Serum levels of TIMP3 and SOX2 decline markedly and the two are closely correlated with renal injury in T2DM patients. Both may be used for an early diagnosis of renal injury in T2DM patients.